Institutional bricolage (re)shaping the different manifestations of state-citizens relations in Mekong hydropower planning - Suhardiman, Diana; Manorom, K.; Rigg, J. (Elsevier, 2022)
Concerns over hydropower development in the Mekong River Basin and elsewhere include not only the overall impacts of dams on basin ecology and economy but also more site-specific impacts on affected communities. While hydropower development is impacting the livelihoods of local communities living along the river, the latter’s views and concerns are often sidelined by top-down hydropower planning. Nonetheless, local communities create and shape their political spaces of engagements in relation to hydropower decision making across scales, albeit through various means and with different results. Taking the planned Pak Beng hydropower dam as a case study and building on the concept of institutional bricolage, we look at: 1) local communities’ responses in Thailand and Laos, including how these are influenced by social movements; 2) how these responses are translated into collective action (or the lack thereof), including in relation to local communities’ (in)ability to negotiate better compensation for their to be impacted livelihoods; and 3) how local communities strategies are embedded in the wider political context and different manifestations of state-citizens relations. We argue that while affected farm households can pursue their interests to secure proper compensation through individual means, this leads to sub-optimal outcomes for affected communities collectively.